Motivasi, Refleksi, dan Konteks: Memahami Kesadaran Kewirausahaan Gen Z di Perguruan Tinggi - Achmad Iqbal; Wiwik Mukholafatul Farida; Mutia Tsalitsa Alawia (Jurnal Proaksi, 2025)
Main Purpose - This study aims to explore how Generation Z students in Indonesia construct entrepreneurial awareness through lived experiences, motivations, and social contexts.Method - A qualitative research design with an interpretative phenomenological analysis (IPA) approach was employed. Data were collected through in-depth semi-structured interviews with three university students interested in entrepreneurship.Main Findings - The findings revealed three major themes: internal motivation, reflective experience, and contextual factors. Participants were intrinsically driven by autonomy, personal growth, and social values, while reflective experiences shaped their entrepreneurial self-awareness. Support from family, peers, and institutions acted as critical enablers in their entrepreneurial journey.Theory and Practical Implications - The study suggests that entrepreneurship education should incorporate reflective and experiential learning to align with Gen Z's identity and motivation. Institutions should also provide tailored support systems to nurture value-driven young entrepreneurs. Novelty - This study offers a multidimensional perspective on entrepreneurial awareness formation among Generation Z by integrating personal meaning-making and sociocultural influences.